2015
DOI: 10.1002/hed.24124
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor‐1 as regulator of tumor‐initiating cell properties in head and neck cancers

Abstract: The inhibition of PAI-1 by PAI-039 or siRNA could suppress head and neck cancer-TICs within head and neck cancer cell lines through the downregulation of Sox2. © 2015 Wiley Periodicals, Inc. Head Neck 38: E895-E904, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
(97 reference statements)
1
21
0
Order By: Relevance
“…We previously discovered that the overexpression of miR-494-3p in aldehyde dehydrogenase 1 (ALDH1)+ CD44+ HNC-TICs inhibited their cancer stemness [ 13 ]. Given that radioresistance is one of the properties of HNC-TICs [ 15 ], the correlation between radiation response and miR-494-3p expression was examined first. As shown in Figure 1 , the expression of miR-494-3p displayed a negative correlation with cell survival after radiation in SAS cells ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously discovered that the overexpression of miR-494-3p in aldehyde dehydrogenase 1 (ALDH1)+ CD44+ HNC-TICs inhibited their cancer stemness [ 13 ]. Given that radioresistance is one of the properties of HNC-TICs [ 15 ], the correlation between radiation response and miR-494-3p expression was examined first. As shown in Figure 1 , the expression of miR-494-3p displayed a negative correlation with cell survival after radiation in SAS cells ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that HNC-TICs displayed a radioresistant feature [ 14 , 15 ]. The present study further examined the function of miR-494-3p and its target gene Bmi1 in the radiation response of the SAS OSCC cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Many targets for pharmaceutical intervention to prevent fibrosis and cardiovascular morbidity after irradiation have been investigated, for example, blocking the renin-angiotensin-aldosterone system through angiotensin-converting enzyme inhibitors and angiotensin receptor blockers or by using statins [ 29 34 ]. Tiplaxtinin (PAI-039, a PAI-1-inhibitor) is an interesting pharmacological agent that has been shown to reduce self-renewal and resistance to radiation in tumor-initiating cells in HNSCC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, substantial studies suggest that PAI-1 at pharmacological levels hinders cancer growth and angiogenesis [123,128,130,131,134-137]. The suppression of PAI-1 by Tiplaxtinin (PAI-039), a specific inhibitor of PAI-1, or siRNA can inhibit tumor-initiating cells within head and neck cancer cell lines via downregulating the sex-determining region Y-box 2 (Sox2) [138]. Some studies reveal that antibodies against PAI-1 may inhibit human cancer cell metastasis in mouse xenograft models [139-141].…”
Section: Plasminogen Activator Inhibitor-1 (Pai-1)mentioning
confidence: 99%